Hydrogen peroxide promotes injury-induced peripheral sensory axon regeneration in the zebrafish skin. - Sandra Rieger; Alvaro Sagasti (PLoS Biology)
Functional recovery from cutaneous injury requires not only the healing and regeneration of skin cells but also reinnervation of the skin by somatosensory peripheral axon endings. To investigate how sensory axon regeneration and wound healing are coordinated, we amputated the caudal fins of zebrafish larvae and imaged somatosensory axon behavior. Fin amputation strongly promoted the regeneration of nearby sensory axons, an effect that could be mimicked by ablating a few keratinocytes anywhere in the body. Since injury produces the reactive oxygen species hydrogen peroxide (H(2)O(2)) near wounds, we tested whether H(2)O(2) influences cutaneous axon regeneration. Exposure of zebrafish larvae to sublethal levels of exogenous H(2)O(2) promoted growth of severed axons in the absence of keratinocyte injury, and inhibiting H(2)O(2) production blocked the axon growth-promoting effects of fin amputation and keratinocyte ablation. Thus, H(2)O(2) signaling helps coordinate wound healing with peripheral sensory axon reinnervation of the skin.